All in the Family : State Capture in Tunisia - Rijkers, Bob; Freund, Caroline; Nucifora, Antonio (Elsevier, 2016)
We examine the relationship between entry regulation and the business interests of former President Ben Ali’s family using firm-level data from Tunisia. Connected firms account for a disproportionate share of aggregate employment, output and profits, especially in sectors subject to authorization and restrictions on FDI. Quantile regressions show that profit and market share premia from being connected increase along the firm-size distribution, especially in highly regulated sectors. These patterns are partly explained by Ben Ali’s relatives sorting into the most profitable sectors. The market shares of connected firms are positively correlated with exit and concentration rates in highly regulated sectors. Although causality is difficult to establish, the results are consistent with the hypothesis that the Ben Ali clan abused entry regulation for private gain at the expense of reduced competition.